Pushing the Boundaries of Scientific Research with the use of Artificial Intelligence tools: Navigating Risks and Unleashing Possibilities - Khan, Naushad Ahmad; Osmonaliev, Kudaibergen; Sarwar, Mohammad Zahed (Nepal Journal of Epidemiology, 2023)
The language of science is communicated through various modes, such as lectures, informal discussions, conferences, and peer-reviewed publications. Artificial Intelligence (AI) based writing tools, like ChatGPT, have recently become increasingly popular due to natural language processing technology advancements. ChatGPT is an AI language model that can generate text close to human writing, making it suitable for tasks such as summarizing literature, composing essays, and producing statistical studies. This technology has the potential to transform scientific communication, but concerns have been raised about its impact on the integrity of research and the role of human researchers. While this technology has advantages such as accelerating the innovation process and enhancing diversity in scientific viewpoints, it is important for the scientific community to debate and envision the consequences of its use. Publishers are working to develop guidelines for its application, which may be capable of future activities such as experiment design and peer review. As we enter the early stages of the AI revolution, it is imperative that the scientific community engages in discourse and contemplate the potential outcomes of this potentially transformative technology. With this in mind, we have outlined relevant topics as a starting point for discussion.